Answer:
Length is : ![x^{2} -3x+2](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-3x%2B2)
Step-by-step explanation:
The width of the rectangular playground is given as = x+3
The area of the playground is given as = ![x^{3} -7x+6](https://tex.z-dn.net/?f=x%5E%7B3%7D%20-7x%2B6)
We have to find the length.
The area of the rectangle is given as :
![A= length*width](https://tex.z-dn.net/?f=A%3D%20length%2Awidth)
So, length can be found as : ![length=\frac{area}{width}](https://tex.z-dn.net/?f=length%3D%5Cfrac%7Barea%7D%7Bwidth%7D)
=> ![\frac{x^{3}-7x+6 }{x+3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B3%7D-7x%2B6%20%7D%7Bx%2B3%7D)
Solving this we get,
Factoring
we get (x-1)(x-2)(x+3)
Using the rational root theorem and assuming a0=6 and a(n)=1
Divisors of a0 = 1,2,3,6
Divisor of a(n) = 1
1/1 is the root of equation. So, factoring out x-1 we get
![(x-1)\frac{x^{3}-7x+6 }{x-1}](https://tex.z-dn.net/?f=%28x-1%29%5Cfrac%7Bx%5E%7B3%7D-7x%2B6%20%7D%7Bx-1%7D)
![\frac{x^{3}-7x+6 }{x-1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B3%7D-7x%2B6%20%7D%7Bx-1%7D)
![x^{2} +\frac{x^{2}-7x+6 }{x-1}](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%5Cfrac%7Bx%5E%7B2%7D-7x%2B6%20%7D%7Bx-1%7D)
![x^{2} +x+\frac{-6x+6}{x-1}](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bx%2B%5Cfrac%7B-6x%2B6%7D%7Bx-1%7D)
dividing
we get -6
So, result becomes ![x^{2} +x-6](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2Bx-6)
Factoring this we get: ![(x-2)(x+3)](https://tex.z-dn.net/?f=%28x-2%29%28x%2B3%29)
![\frac{(x-1)(x-2)(x+3)}{(x+3)}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%28x-2%29%28x%2B3%29%7D%7B%28x%2B3%29%7D)
Cancelling x+3
We get the length as =
or ![x^{2} -3x+2](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-3x%2B2)